The message of the Sermon on the Mount Christian counter-culture - Stott, John Robert Walmsley 1921- (Leicester, UK IVP, 1978)
Includes bibliographical references.
"The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990". Originally published under the title "Christian counter-culture".
Keywords: Bible. N.T. Sermon on the Mount -- commentaries